2014
DOI: 10.3892/ijmm.2014.1860
|View full text |Cite
|
Sign up to set email alerts
|

siRNA-mediated silencing of Wnt5a regulates inflammatory responses in atherosclerosis through the MAPK/NF-κB pathways

Abstract: Previous studies have demonstrated that the aberrant expression of Wnt5a occurs in atherosclerotic lesions. However, the precise role of Wnt5a in the pathogenesis of atherosclerosis remains largely unknown. The present study was undertaken to determine whether the RNA interference of Wnt5a in vivo by adenovirus (Ad)-mediated small interfering RNA (siRNA) transfection is capable of inhibiting the progression of atherosclerosis. Recombinant adenovirus carrying siRNA targeting Wnt5a (Ad-Wnt5a siRNA) was designed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 28 publications
(28 reference statements)
1
30
0
Order By: Relevance
“…ROS are able to regulate MAPK pathway involved in inflammatory process [42, 43]. The current experiment showed that FPA increased the expressions of phosphorylated ERK1/2 and p38 in vivo and in vitro , and ERK1/2 inhibitor PD98059 and p38 inhibitor SB203580 reduced FPA-induced CRP expression in vitro , implicating that the activated ERK1/2 and p38 participate in FPA-induced CRP production.…”
Section: Discussionmentioning
confidence: 75%
“…ROS are able to regulate MAPK pathway involved in inflammatory process [42, 43]. The current experiment showed that FPA increased the expressions of phosphorylated ERK1/2 and p38 in vivo and in vitro , and ERK1/2 inhibitor PD98059 and p38 inhibitor SB203580 reduced FPA-induced CRP expression in vitro , implicating that the activated ERK1/2 and p38 participate in FPA-induced CRP production.…”
Section: Discussionmentioning
confidence: 75%
“…It has also been reported that activation of THP-1 cells by Wnt5a via the non-canonical pathway involves JNK and NF-κB activation [57]. Recently, Yang L et al [58] reported that the knockdown of Wnt5a in ApoE −/− mice could inhibit the NF-κB and MAPK signaling pathways, thereby mitigating the progression of atherosclerosis.…”
Section: Wnt5a Expression In Macrophages Is Regulated By Inflammatmentioning
confidence: 99%
“…Sequences were listed as follows: Special: 5¢-GAA GCC CAU UGG AAU AUU ATT-3¢ (sense) and 5¢-UAA UAU UCC AAU GGG CUU CTT-3¢ (antisense); Nonspecial: 5¢-UUC UCC GAA CGU GUC ACG UUU-3¢ (sense) and 5¢-ACG UGA CAC GUU CGG AGA AUU-3¢ (antisense). The Wnt5a siRNA recombinant adenovirus (Ad-Wnt5a-siRNA) was constructed as previously described (Yang et al, 2014). Briefly, the synthesized siRNA sequences were amplified and subcloned into pAdTrack-cytomegalovirus (CMV) plasmids (Stratagene-Agilent Technologies, Waldbronn, Germany).…”
Section: Construction Of Wnt5a Sirna Recombinant Adenovirusmentioning
confidence: 99%